Dysbiosis versus diabesity: Pathological signaling and promising therapeutic strategies. Issue 5 (May 2023) - Sharma, Arun K.; Sharma, Akash; Lal, Samridhi; Kumar, Ashish; Yadav, Nirmala K.; Tabassum, Fauzia; Sayeed Akhtar, Md.; Tarique Imam, Mohammad; Saeed Almalki, Ziyad; Mukherjee, Monalisa
Highlights: Report reveals the pathological cascade in metabolic disorders. Molecular signalling explain how gut bacteria leads to diabesity. Report explains the vicious circle of pathology between diabesity & dysbiosis. Report highlights the involved diverse metabolites, receptor & microorganism. Understanding of molecular events help to establish the novel therapies. Abstract : A healthy life depends on the inseparable relationship between a host and the gut microbiota. A healthy gut microbiota regulates intestinal integrity, whereas an unbalanced gut microbiota contributes to junctional remodeling and leads to dysbiosis. Bacterial infiltration and dysbiosis are reported to activate a series of pathological cascades that trigger metabolic abnormalities, including diabesity. Conversely, recent studies revealed that the incidence of dysbiosis itself is fuelled by diabesity. In this review, we highlight the molecular aspects of multifaceted pathological signaling between dysbiosis and diabetes that could pave the way for new drug discovery. Moreover, to reinstate the gut microbiota and restrict the epidemic of dysbiosis and diabesity, we also scrutinize a promising therapeutic strategy that can challenge the pathological interlink.